Assessment and characterization of waste material used as backfilling in an abandoned mine - Shirin S.; Jamal A.; Emmanouil C.; Singh V.P.; Yadav A.K. (My University, 2025)
Overburden is the earth material removed during opencast mining, which is typically not contaminated with toxic materials. After mining operations, overburdens are dumped on exhausted mining sites. However, some opencast mines are not properly backfilled, and this causes harmful environmental effects, such as leaching of acid mine drainage. The flyash produced from thermal power plants is also a major waste that must be disposed of environmentally friendly. This study focuses on filling the voids of an abandoned mine with a mixture of 70% overburden + 30% flyash. A considerable improvement in acid mine drainage characteristics was found after either adding overburden or an overburden and flyash mixture. Sustainable management of coal mines should include the careful restoration of exhausted mines, which can be made possible by repurposing relevant industrial waste. © 2022 Taylor & Francis Group, LLC.